Description of the marine predator Sericomyxa perlucida gen. et sp. nov., a cultivated representative of the deepest branching lineage of vampyrellid amoebae (Vampyrellida, Rhizaria). (21st July 2021) - More, Kira; Simpson, Alastair G. B.; Hess, Sebastian
Abstract: The vampyrellids (Vampyrellida, Rhizaria) are naked amoebae of considerable genetic diversity. Three families have been well‐defined (Vampyrellidae, Leptophryidae, and Placopodidae), but most vampyrellid lineages detected by environmental sequencing are poorly known or completely uncharacterized. In the brackish sediment of Lake Bras D'Or, Nova Scotia, Canada, we discovered an amoeba with a vampyrellid‐like life history that was morphologically dissimilar from previously known vampyrellid taxa. We established a culture of this amoeba, studied its feeding behavior and prey range specificity, and characterized it with molecular phylogenetic methods and light and electron microscopy. The amoeba was a generalist predator (i.e. eukaryotroph), devouring a range of marine microalgae, with a strong affinity for some benthic diatoms and Chroomonas . Interestingly, the amoeba varied its feeding strategy depending on the prey species. Small diatoms were engulfed whole, while larger species were fed on through extraction with an invading pseudopodium. The SSU rRNA gene phylogenies robustly placed the amoeba in the most basal, poorly described lineage ("clade C") of the Vampyrellida. Based on the phylogenetic position and the distinct morphology of the studied amoeba, we here describe it as Sericomyxa perlucida gen. et sp. nov., and establish the new vampyrellid family Sericomyxidae for "clade C."